Pengaruh Latihan Kecepatan Terhadap Kecepatan Menggiring Bola Pemain Futsal Junior Fc Patriot Penjaskesrek Unpatti Ambon - Johanna Matitaputty (Jurnal Ilmiah Wahana Pendidikan, 2019)
The effort to increase the optimal dribbling speed is one way to do this by applying speed training. Speed ​​training is very effective in Futsal games especially Speed ​​in dribbling. This study aims to find out whether there is an effect of speed training on the speed of dribbling of Junior Fc Patriot Fc Patriot players in Unpatti Insurance, Ambon. the percentage results obtained from statistical data analysis using the t-test formula, it turns out that the tcount is 6.726 and ttable is significant at 5% (N-1 = 14) = 2.14, because tcount is greater than ttable so Ha is accepted and H0 is rejected, meaning that there is an effect of speed training on Speed ​​driving the ball of Junior futsal player Fc Patriot Unkatti Ambon Sport Team. Thus it was concluded that there was the effect of speed training on Speed ​​leading to the ball of Junior futsal players Fc Patriot, Unpatti Ambon Military Team.